Acquired dysfibrinogenemia secondary to multiple myeloma - Kotlín, Roman; Sobotková, Alzbeta; Riedel, Tomás; Salaj, Peter; Suttnar, Jirí; Reicheltová, Zuzana; Májek, Pavel; Khaznadar, Tarek; Dyr, Jan E (Acta haematologica, 2008)
Abnormal coagulation properties indicative of a dysfibrinogen were found in the plasma of a 72-year-old male with multiple myeloma (IgGkappa, stage IIIA). The patient had high paraprotein concentration (85.75 g/l) and prolonged thrombin time (76.8 s), activated partial thromboplastin time (39.5 s), prothrombin time (23.5 s) and reptilase time (72.0 s). The fibrinogen level was increased. The fibrin polymerization induced by both thrombin and reptilase was impaired. Scanning electron microscopy revealed abnormal clot morphology. After six months of treatment, the paraprotein level decreased (19.48 g/l) and coagulation normalized as well as fibrin polymerization and fibrin clot morphology. It was found that the paraprotein interacts with the gamma-chain of fibrinogen. Acquired dysfibrinogenemia associated with multiple myeloma was diagnosed in the 72-year-old patient.
Keywords: Blood Coagulation Tests; paraproteiny; Humans; Multiple Myeloma; Aged; Microscopy, Electron, Scanning; výsledek terapie; senioři; lidé; Paraproteins; fibrinogen; mnohočetný myelom; Afibrinogenemia; Peptide Fragments; Male; mikroskopie elektronová rastrovací; Treatment Outcome; afibrinogenemie; peptidové fragmenty; vyšetření krevní srážlivosti; Fibrinogen; mužské pohlaví; Fibrin; fibrin